2013
DOI: 10.3109/1354750x.2013.773079
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis betweenMDR1gene polymorphisms and risk of hepatocellular carcinoma in Chinese population

Abstract: The objective of this study was to evaluate the association between MDR1 gene polymorphisms and hepatocellular carcinoma (HCC) risk. Genomic DNA of 1431 subjects was extracted from peripheral blood and genotyping was performed using the created restriction site-polymerase chain reaction (CRS-PCR). We found that the c.1465C > T single nucleotide polymorphisms (SNP) increased HCC risk in all genetic models (p < 0.05) and the allele-T of c.1465C > T may contribute to the risk of HCC. No significantly increased HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Therefore, Chen et al, indicated that the C3435T polymorphism may be a positive candidate molecular marker for the prognosis of HCC (Chen et al, 2011). Yang et al (2013) found that the c.1465C>T polymorphism may contribute to the risk of HCC, while no significantly increased HCC risk was detected in c.159G>T polymorphism (Yang et al, 2013). However, results from these observations remain conflicting rather than conclusive.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Therefore, Chen et al, indicated that the C3435T polymorphism may be a positive candidate molecular marker for the prognosis of HCC (Chen et al, 2011). Yang et al (2013) found that the c.1465C>T polymorphism may contribute to the risk of HCC, while no significantly increased HCC risk was detected in c.159G>T polymorphism (Yang et al, 2013). However, results from these observations remain conflicting rather than conclusive.…”
Section: Discussionmentioning
confidence: 47%
“…It has been reported that the MDR1 gene is regarded as one of the most important candidate genes for influencing on the susceptibility to HCC. The potential associations between several MDR1 genetic polymorphisms and HCC susceptibility have been assessed (Wu et al, 2007;Chen et al, 2009;Chen et al, 2011;Ren et al, 2012;Gao, 2013;Yang et al, 2013). Wu and his colleagues reported that the MDR1 gene polymorphisms (such as C1236T, G2677A/T, and C3435T) could be valuable molecular markers for HCC recurrence after liver transplantation (Wu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that the multidrug resistance 1 gene (MDR1) is an important candidate gene influencing HCC (Wu et al, 2007;Vander Borght et al, 2008;Chaijaroenkul et al, 2011;Chen et al, 2009Chen et al, , 2011Geng et al, 2011;Yu et al, 2011;Ren et al, 2012;Sun et al, 2012;Gao, 2013;Li et al, 2013;Yang et al, 2013). MDR1 is a polygenetic gene and many genetic polymorphisms, such as G159T, T335C, C1236T, C1465T, G2677A/T, C3435T, A3073C, and A4125C, have been reported to have possible associations with the risk of HCC (Cavaco et al, 2003;Pechandova et al, 2006;Wu et al, 2007;Vander Borght et al, 2008;Chen et al, 2009Chen et al, , 2011Yu et al, 2011;Ren et al, 2012;Gao, 2013;Yang et al, 2013). Several studies suggested that MDR1 genetic polymorphisms influenced HCC risk (Wu et al, 2007;Chen et al, 2009Chen et al, , 2011Ren et al, 2012;Gao, 2013;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%